Exploring Physicians' Comfort Level with Opioids for Chronic Noncancer Pain - Martin N Scanlon; Urmil Chugh (Pain Research and Management)
OBJECTIVE: To explore the attitudes of family physicians (FPs) toward the use of opioids in the management of chronic noncancer pain (CNCP) in the Calgary Health Region (CHR), Calgary, Alberta.